2006
DOI: 10.1097/01.mlg.0000232495.77308.46
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Tympanoplasty for Total or Near‐Total Perforation: Prognostic Factors

Abstract: Successful grafting of near-total and total tympanic membrane perforations occurred in 91% of the cases and was independent of demographic, disease, and technical variables. Disease variables (preoperative ABG and status of malleus handle) had a greater prognostic value on postoperative ABG than other variables. In revision tympanoplasty, mastoidectomy is associated with a better functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 13 publications
3
62
2
Order By: Relevance
“…Success rates with these techniques range from 77% to 96% . Higher success rates are found using the lateral graft approach for large and anterior perforations, which have a reduced rate of closure overall …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success rates with these techniques range from 77% to 96% . Higher success rates are found using the lateral graft approach for large and anterior perforations, which have a reduced rate of closure overall …”
Section: Discussionmentioning
confidence: 99%
“…Exposure of the anterior middle ear is limited, and the success rate is lower for larger perforations . In the overlay (lateral) approach, the squamous layer of the TM is removed, and the graft is placed lateral to the tympanic annulus . This technique has higher success for large and anterior perforations, but is associated with prolonged surgery and risk of blunting of the anterior angle and graft lateralization.…”
Section: Introductionmentioning
confidence: 99%
“…However, some retrospective studies show that there is no difference in outcomes of graft success rate or post-operative hearing with regard to whether mastoidectomy is performed in addition to tympanoplasty (Balyan et al, 1997;Mishiro et al, 2001). Mastoidectomy may be indicated to reduce the burden of disease in cases with abscess formation in the mastoid, tympanoplasty or recalcitrant disease (Collins et al, 2003;Angeli et al, 2006).…”
Section: Surgerymentioning
confidence: 99%
“…Regardless of what techniques used, in cases which the malleus handle is in close relationship with perforation, the squamous epithelium covering the malleus handle should be desepithelised. According to several authors the malleus handle has a key role in the success of the tympanoplasty and it is worthwhile to preserve it (2, 3, 5). In contrast some other authors reported that the presence of the malleus handle was not an important prognostic factor (8, 9).…”
Section: Discussionmentioning
confidence: 99%